Remineralization Potential of Nanohydroxyapatite Toothpaste Compared with Tricalcium Phosphate and Fluoride Toothpaste on Artificial Carious Lesions - Apa Juntavee; Niwut Juntavee; Praewpan Hirunmoon (Hindawi Limited, 2021)
Introduction. Nanohydroxyapatite (nano-HA) has been utilized as an alternative agent for dental enamel remineralization. This study compared remineralization potential of nano-HA toothpaste (NHT), functionalized tricalcium phosphate toothpaste (TCPT), and fluoride toothpaste (FT) on carious lesions. Materials and Methods. Sixty extracted human premolars were prepared for artificial carious lesions with synthetic polymer gel. Samples were divided into four groups according to testing agents: NHT, TCPT, FT, and one group with no treatment (NT). Each group was subjected to pH-cycling with the application of toothpaste in slurry form twice a day (2-min each) for 10 days. Surface microhardness was measured before demineralization, after demineralization, and after pH-cycling. Hardness at different periods, percentage of hardness recovery (% HR), and percentage of remineralization potential (%RP) were determined and statistically analyzed with ANOVA and Tukey comparisons (α = 0.05). Polarized light microscopy (PLM) was utilized to assess lesion depth. Results. Significant remineralization of carious lesions was observed among different toothpastes compared to NT (p<0.05). No significant difference in remineralization potential was found among NHT, TCPT, and FT (p>0.05). No significant difference in % HR and % RP was seen among NHT, TCPT, and FT (p>0.05). PLM indicated a greater decrease in carious depth upon using NHT compared to TCPT and FT, with minimal increase in depth for NT. Conclusions. NHT has comparable capability to TCPT and FT in hardness recovery. However, decrease in carious depth was evidenced with PLM for NHT more than TCPT and FT. Thus, NHT was suggested as a potential remineralization product for treating initial carious lesions. Clinical Significance. The study showed that NHT had the potential to remineralize artificial carious lesion. It was confirmed in potential in the lesion depth reduction and forming a new enamel layer. NHT showed its capability as an alternative for dental caries therapeutic.